Subacute infective endocarditis presenting as upper abdominal pain - Benny, Bobithamol K.; Daimei, Stephen; Mohammed, Thouseef; Ering, Prity; Dutta, Tatagata (International Journal of Advances in Medicine, 2020)
Splenic abscess develops in 3-5% of patients with infective endocarditis. In more protracted subacute cases of infective endocarditis, symptoms and signs such as anorexia, weight loss, weakness, arthralgia and abdominal pain may occur in 5-30% of patients and thereby misleading the clinician to pursue incorrect diagnosis such as malignancy, connective tissue disease, or other chronic infection or systemic inflammatory disorders. Left upper quadrant pain can be a presenting symptom in a patient with IE, if it is complicated by septic embolization to spleen. Here reported a case of subacute infective endocarditis complicated with splenic embolization in a 34-year-old male with diabetic nephropathy and ischemic dilated cardiomyopathy, presented as acute abdominal pain.